Interplay between content knowledge and scientific argumentation - BEKİROĞLU, FERAL (EURASIA, 2016)
This research study aimed to analyze the relationship between content knowledge and argumentation by examining students' prior subject matter knowledge and their production of arguments as well as by comparing students' arguments with their knowledge-in-use during scientific argumentation sessions. A correlational research design was carried out for this research by using qualitative and quantitative methods. The participants of the study were 13 senior pre-service physics teachers studying in a large urban state university. Six scientific argumentation sessions in different contexts under different contents were implemented in the methods course where pre-service teachers meet for 5 h per week. Written and oral data were collected by using a variety of methods for different purposes. Toulmin's Argument Pattern was used to evaluate the arguments while content knowledge was analyzed by the model developed by Chi and Roscoe (2002). Some of the conclusions drawn from the study are as follows: First, a positive relationship exists between individuals' content knowledge they use and quantity of arguments they produce during a scientific argumentation. Second, some conditions influence the relationship. Third, there are number of interactional factors affecting production of arguments. Fourth, learners' characteristics has an impact on their engagement with argumentation. Suggestions and implications have been made.
Keywords: Argumentation; content knowledge; interaction; physics; STUDENTS ARGUMENTATION; CONCEPTUAL KNOWLEDGE; DIALOGUE THEORY; SCIENCE; DISCOURSE; EDUCATION; COGNITION; GENETICS; PLACE